심장수술 받은 영아의 영양중재프로그램 개발 및 적용 - 문주령; 조용애; 민선인; 양지혁; 허준; 정연이; Moon, Ju-Ryoung; Cho, Yong Ae; Min, Sun-In; Yang, Ji-Hyuk; Huh, June; Jung, Yeon-Yi (Journal of Korean Academy of Nursing, 2009)
Purpose: Despite recent advances in the surgical and postoperative management of infants with congenital heart disease, nutritional support for this population is often suboptimal. The purpose of this study was to develop a nutritional program for the postoperative period for infants who have had cardiac surgery and to evaluate effects of the program. Methods: A quasi-experimental design with pretest and posttest measures was used. A newly developed nutritional program including a feeding protocol and feeding flow was provided to the study group (n=19) and usual feeding care to the control group (n=19). The effects of the feeding program were analyzed in terms of total feed intake, total calorie intake, gastric residual volume, and frequency of diarrhea. Results: Calorie intake and feeding amount in the study group were significantly increased compared to the control group. However, the two groups showed no significant differences in gastric residual volume and frequency of diarrhea. Conclusion: The results indicate that the nutritional program used in the study is an effective nursing intervention program in increasing feeding amount and calorie intake in infants postoperative to cardiac surgery and does not cause feeding-related complications.